Artificial Intelligence and Divorce Law: Problems and Challenges of Divorceify for Indonesia’s Legal Future - Kamalludin, Iqbal; Pratami, Bunga Desyana (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2024)
Divorceify is an Artificial Intelligence (AI)-based platform designed to assist in managing divorce processes within a divorce accounting system. However, applying this platform in Indonesia’s legal system may face several challenges. This article examines the extent of Divorceify’s role and influence within the judicial system. It also delves into the challenges and future impacts of using Divorceify in Indonesia’s legal system. Using normative research methods with a conceptual approach, this article asserts that in the context of Indonesian law, the adoption of such technology faces various obstacles, including alignment with local legal frameworks, cultural sensitivities, access and education on technology, and data privacy issues. Indonesia’s legal system can adapt to this innovation in order to improve efficiency and fairness in divorce proceedings, as it is seen as capable of enhancing efficiency, reducing costs, providing fairer outcomes, and alleviating administrative burdens on courts. Additionally, critical obstacles must be addressed to ensure successful integration, especially regarding legal ethics and personal data protection. With the appropriate regulatory, ethical, and technological frameworks, AI-based divorce management tools like Divorceify hold significant potential to improve Indonesia’s judicial system.